KUKA ROBOT LANGUAGE: MOTION CONTROL OF KUKA ROBOT - Mohamed Zuhri, Ahmad Syazni Afham (IRC, 2018)

(untitled)
Industrial robots have been widely used in many areas for the properties such as low cost, high flexibility and relatively large working space. Most commercial manufacturer of industrial robots require their robot to be programmed in a proprietary language tailored to the domain. However, these languages oftentimes suffer from shortcomings such as controller specific design, limited expressiveness and lack of extensibility. For the reason, in this project to control motion of the robot using Kuka Robot Language (KRL) for programming industrial robots on top of general-purpose language. Although being a very flexible approach to programming industrial robots, a fully-fledged language can be too complex for simple tasks. Based on the result, the author managed to communicate the KRL with Kuka Robot after repairing and do some maintenance on the robot in the last 11 years be abandoned. After successful communicate and control the Kuka Robot with KRL, the author can conclude that the objective of this project has been achieved. The objectives of this project are to apply and communicate the robot arm with KRL for motion control of robot manipulator.